Supply Chain Integration of Procurement and Logistics Operation for Enhancing Operational Competencies: a Case Study of Malaysia’s Oil and Gas Company - Tie, Ting Huat; Cheng, Sheila (AeU, 2015)
Studies indicated that supply chain integration (SCI) increases the operational competencies. Over the past 34 years, various form of integration such high integrity information exchange, strategic sourcing has been studied and evidenced in operational performance improvement. The local contractors/service providers for project of